2013
DOI: 10.3168/jds.2012-5624
|View full text |Cite
|
Sign up to set email alerts
|

Effect of photoperiod and heat stress in the third trimester of gestation on milk production and circulating hormones in dairy goats

Abstract: The influence of photoperiod manipulation in the dry period was examined in dairy goats experiencing environmental heat stress. Multiparous Israeli Saanen goats were blocked at dry off (∼60 d prepartum) into 2 groups of 4 goats each based on body weight, previous milk production, and detected embryo number. Treatments consisted of long-day (16 h light:8 h dark) and short-day (8 h light:16 h dark) photoperiods (LDPP and SDPP, respectively). Heat-stress conditions were applied by manipulating the environment of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
26
1
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(44 citation statements)
references
References 31 publications
10
26
1
3
Order By: Relevance
“…Prolactin (PRL) is a potent lactogen and stimulates homeorhetic and mammary specific processes for adaptation to lactation. Circulating PRL levels are increased in ruminants exposed to LDPP (16 h of light and 8 h of dark) (Mabjeesh et al 2007;Dahl et al 2012;Mabjeesh et al 2013), and this hormonal change is hypothesized to mediate the homeorhetic response to changes in photoperiod (Dahl 2008). Our previous studies using a mouse mammary epithelial cell line showed that PRL functions as an input to the mammary clock as treatment with PRL significantly increased ARNTL expression levels, and timing of application shifted phase of expression (Casey TM et al 2014).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prolactin (PRL) is a potent lactogen and stimulates homeorhetic and mammary specific processes for adaptation to lactation. Circulating PRL levels are increased in ruminants exposed to LDPP (16 h of light and 8 h of dark) (Mabjeesh et al 2007;Dahl et al 2012;Mabjeesh et al 2013), and this hormonal change is hypothesized to mediate the homeorhetic response to changes in photoperiod (Dahl 2008). Our previous studies using a mouse mammary epithelial cell line showed that PRL functions as an input to the mammary clock as treatment with PRL significantly increased ARNTL expression levels, and timing of application shifted phase of expression (Casey TM et al 2014).…”
Section: Resultsmentioning
confidence: 99%
“…PRL was measured using a sandwich ELISA assay developed in our laboratory (Mabjeesh et al 2007;Mabjeesh et al 2013). Briefly, ELISA plates (Nunc, Thermo, Denmark) were coated with 1 µg/ml of monoclonal mouse anti-prolactin IgG1 (clone 6F11, Abnova, Taiwan) diluted in carbonate-bicarbonate buffer, pH 9.6 (Thermo, IL, USA) and incubated in a humidified chamber at 4°C overnight.…”
Section: Prolactin Elisamentioning
confidence: 99%
“…The reduction in serum PRL concentration with exposure to ergot alkaloids via grazing endophyte-infected tall fescue pastures or consumption of endophyte-infected tall fescue seed is a classical response observed in sheep (Elsasser and Bolt, 1987; Emile et al, 2000; Parish et al, 2003), cattle (Emile et al, 2000; Watson et al, 2004; Koontz et al, 2012; Stowe et al, 2013), and horses (McCann et al, 1992). It has been documented in multiple species that as parturition approaches maternal serum PRL concentration increases (Chamley et al, 1973; Bryant and Chamley, 1976; Forsyth, 1986) and this increase is hypothesized to be important for maternal lipid metabolism, mammary growth, and milk production and secretion (Hooley et al, 1978; Banchero et al, 2006; Mabjeesh et al, 2013). The levels of PRL reported here for the E− group are consistent with previous reports; however, the drastically lower levels observed at d 130 for E+ could indicate post-partum issues with ewe metabolism and mammary growth, which would negatively impact postnatal lamb growth.…”
Section: Resultsmentioning
confidence: 99%
“…Konsekuensi dari cekaman panas atau toleransi panas yang rendah secara langsung adalah terjadinya penurunan produktivitas ternak, baik pertumbuhan, produksi susu, maupun reproduksi. Mabjeesh et al (2013) melaporkan bahwa terjadi penurunan produksi susu pada kambing yang terkena cekaman panas. Parameter lain yang menunjukkan cekaman panas adalah adanya perubahan fisiologis dan tingkahlaku, yaitu penurunan nafsu makan dan metabolisme, peningkatan konsumsi air minum, peningkatan pengeluaran panas melalui evaporasi; penurunan konsentrasi hormon metabolis dalam darah, peningkatan suhu tubuh, frekuensi pernafasan, dan denyut jantung (Qisthon dan Suharyati, 2007;Aguilar et al, 2010;dan Seixas et al, 2017).…”
Section: Pendahuluanunclassified